The retromandibular transparotid approach vs. retromandibular retroparotid approach for the mandibular condyle - Shaheen Ahmed; Reema Usmani; Abdul Hafeez Shaikh; Usman Ashraf; Syeda Noureen Iqbal; Abdullah Salman; Anwar Ali (Universidade Estadual de Campinas, 2021)
Aim: The mandible is regarded as a frequently fractured bone in patients who present with maxillofacial trauma accounting for almost 15.5% to 59% of all facial fractures. Managing condylar trauma has remained to be a point of contention amongst experts, regardless of the advances in surgical modalities and methodologies, and the treatment plan is often determined by the preference and the experience of the surgeon. There exist various approaches in the literature, each with its own specific benefits and drawbacks. With this study, we aimed to evaluate the prevalence of post-operative complications in patients who experienced ORIF by means of the retromandibular approach, by comparing the outcomes of one group having undergone transparotid surgery, with another that underwent retroparotid surgery. Methods: An experimental trial was undertaken. Convenience sampling was done from among the cases of condylar neck and base fracture visiting the department of OMFS, Dow University of Health Sciences from January 2017 to December 2019. An overall 26 patients were divided into 2 groups of 13 members each; one was managed using Open Reduction Internal Fixation (ORIF) by means of a retromandibular transparotid approach while the other group was treated with ORIF by means of a retromandibular retroparotid approach. A 6 month follow-up was done to assess range of active motion, occlusion, and complications such as deviation/deflection, neural injury, infections, sialocele, salivary fistulae and Frey's syndrome in both groups. Results: There was no statistically significant difference between the two groups in terms of inter-incisal opening, right and left lateral movements, or protrusion. One patient in the retroparotid group had deviation on mouth opening (7.69%), while one in the transparotid group reported with infection (7.69%), and 2 developed post operative seromas (15.38%). None had persisting facial nerve palsy at 6 months. Conclusion: We find no significant disparity between the 2 approaches at a follow-up of 6 months; therefore, the primary determining factor for selection of either technique is surgeon preference and appropriate case selection.